Job Stress and Work Environment as Determinants of Employee Performance in the Indonesian Private Sector - Lubis, Muhammad Arif; Sentosa, Ilham; Weber, Gerhard Wilhelm (Journal Of Management Analytical and Solution (JoMAS), 2025)
Employee performance is a critical factor in achieving organizational goals and sustaining competitive advantage. This study investigates the influence of job stress and work environment on employee performance at PT. Rahayu Permai. Employing a quantitative research design, data were collected through structured questionnaires distributed to employees and analyzed using multiple linear regression techniques. The results indicate that job stress has a negative and significant effect on employee performance, while the work environment exerts a positive and significant influence. These findings highlight the importance of organizational efforts to minimize work-related stress and improve workplace conditions in order to enhance employee productivity and overall performance